Water Quality Indices for Assessing Heavy Metal Pollution in Winongo River and Gajahwong River Yogyakarta-Indonesia - Margaretha Widyastuti; Galih Dwi Jayanto; Muhammad Ridho Irshabdillah; Lintang Nur Fadlillah (School of Postgraduate Studies, Diponegoro Univer, 2024)
Abstract Winongo and Gajahwong Rivers traverse three regions: Sleman Regency, Yogyakarta City, and Bantul Regency. Both rivers' water quality was assessed using two water quality indices specified for detecting only the heavy metal presence, namely Heavy Metal Pollution Index (HPI) and Pollution Index (PI). Details on river water quality were a series of monitoring data from 2017 until 2020 that comprised eleven parameters: pH, BOD, COD, NH3N, TSS, Total Coli, oil and grease, Fe, Cu, Cd, Cr, and Pb. The results indicate that the heavy metal contents of Winongo and Gajahwong Rivers meet the class II water quality standard. Non-metal parameters, namely COD and TSS, are present in small amounts and below the upper thresholds. The HPI values of Winongo and Gajahwong Rivers were 3.15 and 2.29, respectively, or categorized as ‘excellent’. Similarly, based on the PI values (0.78 and 0.72, respectively), both rivers' water quality fell into the category of ‘good’.